All Green Solvents for Fabrication of CsPbBr3 Films for Efficient Solar Cells Guided by the Hansen Solubility Theory. Issue 4 (30th January 2020) - Cao, Xiaobing; Zhang, Guoshuai; Cai, Yifan; Jiang, Long; He, Xin; Zeng, Qingguang; Wei, Jinquan; Jia, Yi; Xing, Guichuan; Huang, Wei
Abstract : Toxic solvents used in the fabrication of perovskite solar cells are an obstacle for their commercialization. Replacing those toxic solvents with green solvents is very important for both ecological environment safety and the health of operators working in manufactory and labs. CsPbBr3 ‐based solar cells have attracted increasing attention due to its high stability. Herein, high‐quality CsPbBr3 films are prepared using all green solvents based on a two‐step spin‐coating method. In the first step, a green solvent system of polyethylene glycol (PEG) with the addition of γ‐butyrolactone is used for preparing PbBr2 solutions by matching the Hansen solubility parameters (HSPs) between PbBr2 and the mixed solvent system. By optimizing the HSPs and viscosity, a new complex of PbBr2 ·(PEG) is formed by spin‐coating from the PbBr2 solution, followed by acetic acid dropping while spinning. In the second step, green water is used to dissolve CsBr to prepare a high concentration CsBr/H2 O solution. High‐quality CsPbBr3 films with full coverage are obtained by spin‐coating CsBr/H2 O solution onto the PbBr2 ·(PEG) films after annealing. As a result, a solar cell with configuration of fluorine‐doped tin oxide/TiO2 /CsPbBr3 /carbon exhibits a power conversion efficiency of 8.11% due to its high‐quality harvest layer. Abstract : High‐quality CsPbBr3 films and efficient perovskite solar cells are fabricated through a two‐step method from all green solvents with the assistance of the Hansen solubility theory.